2020
DOI: 10.1002/jmv.26423
|View full text |Cite
|
Sign up to set email alerts
|

HIV p17 enhances T cell proliferation by suppressing autophagy through the p17‐OLA1‐GSK3β axis under nutrient starvation

Abstract: Nutrient starvation is a common phenomenon that occurs during T cell activation. Upon pathogen infection, large amounts of immune cells migrate to infection sites, and antigen‐specific T cells are activated; this is followed by rapid proliferation through clonal expansion. The dramatic expansion of cells will commonly lead to nutrient shortage. Cellular autophagy is often upregulated as a way to sustain the body's energy requirements. During infection, human immunodeficiency virus (HIV) co‐opts a series of hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…5 B). Our previous study showed that OLA1 directly interacted with GSK3β and inhibited its activity [ 21 , 22 ], which is also proved by other study [ 23 , 24 ]. Meanwhile, GSK3β can phosphorylate HIF1α and facilitate its degradation [ 25 ], which can explain why HIF1α decreased in OLA1-KO CRC cell lines.…”
Section: Resultssupporting
confidence: 67%
“…5 B). Our previous study showed that OLA1 directly interacted with GSK3β and inhibited its activity [ 21 , 22 ], which is also proved by other study [ 23 , 24 ]. Meanwhile, GSK3β can phosphorylate HIF1α and facilitate its degradation [ 25 ], which can explain why HIF1α decreased in OLA1-KO CRC cell lines.…”
Section: Resultssupporting
confidence: 67%
“…The inhibition of apoptosis is not the only mechanism by which the HIV-1 matrix protein alters the biological activities of immune cells, given that it also acts as a major factor in suppressing the autophagic process in immune T cells, especially under glucose starvation conditions. According to Lu et al, HIV p17 interacts with Obg-like ATPase 1 (OLA1), resulting in the hyperactivation of the downstream effector glycogen synthase kinase-3 beta (GSK3β), a critical regulator in the T cell autophagic process ( Figure 3 b) [ 48 ].…”
Section: P17: Viral Matrix Protein And/or Deregulator Virokine?mentioning
confidence: 99%
“…Primary human monocytes AP-1 transcription factor activation Inflammation (MCP-1 secretion) [46] Plasmacytoid dendritic cells (pDCs) Down-regulation of nucleophosmin, heat shock protein 70 and eukaryotic translation initiation factor 5B Cell survival, resistance to apoptotic stimuli, increased proliferation [47] Human T cells Obg-like ATPase 1 (OLA1) and hyperactivation of glycogen synthase kinase-3 beta (GSK3β) Autophagy inhibition [48] Human B cells PTEN/PI3K/Akt pathway activation Apoptosis inhibition, cell cycle promotion and cancer progression [18,49] Breast cancer cells line (MDA-MB231) ERK/MAPK pathway activation Enhance cell migration and invasiveness [50] Human endothelial cells (ECs) PI3K/Akt and MEK/ERK1/2 Angiogenic activity [51] Primary human lymph nodederived lymphoid endothelial cells (LN-LECs) PI3K/Akt and MEK/ERK1/2 Lymphangiogenic activity [52] p24 Dendritic cells (DCs) STAT1 and IRF3 pathways activation Inflammation (INF production) [53] Leukemic monocyte cell line (THP-1)…”
Section: Inhibition Of Protein Kinase C (Pkc) Activity and Calcium Mo...mentioning
confidence: 99%